Investment and divestment policies of multinational corporations in Europe - Bulcke, D. van den. (Farnborough, Eng. : Saxon House ; Brussels : European Centre for Study and Information on Multinational Corporations, 1979)
This book presents an extensive overview of investment and divestment policies of multinational corporations in Europe. It is a collection of four separate papers gathered under the auspices of the European Centre for Study and Information on Multinational Corporations. This collection illustrates the objectives, motivations and constraints which determine attitudes, actions, and problems of not only governments and firms but labourers and consumers in Europe.
Includes bibliographical references.
lje 24/04/2018
Loans
Keywords: Investments, Foreign; International business enterprises